1996
DOI: 10.1074/jbc.271.8.4148
|View full text |Cite
|
Sign up to set email alerts
|

Activation of a Recombinant Petunia Glutamate Decarboxylase by Calcium/Calmodulin or by a Monoclonal Antibody Which Recognizes the Calmodulin Binding Domain

Abstract: To date, only plants have been shown to possess a form of glutamate decarboxylase (GAD) that binds calmodulin. In the present study, a recombinant calmodulin-binding 58-kDa petunia GAD produced in Escherichia coli was purified to homogeneity using calmodulin-affinity chromatography, and its responsiveness to calcium and calmodulin was examined in vitro. At pH 7.0 -7.5, the purified recombinant enzyme was essentially inactive in the absence of calcium and calmodulin, but it could be stimulated to high levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
99
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 148 publications
(103 citation statements)
references
References 55 publications
4
99
0
Order By: Relevance
“…This may reflect differences among organisms with respect to the cellular levels of NADK substrates. The high affinity of Arabidopsis NADK for CaM (S 0.5 of 2.2 nM) is consistent with reports on other plant NADKs (Harmon et al, 1984;Lee et al, 1997;Delumeau et al, 2000) and other plant CaM-binding proteins (Snedden et al, 1996;Bouche et al, 2002;Zhang et al, 2002;Chandok et al, 2003). Similarly, the S 0.5 value for Ca 21 (0.8 mM) suggests stimuli that elevate Ca 21 from resting levels in vivo may elicit a CaM-modulated NADK response.…”
Section: Discussionsupporting
confidence: 74%
“…This may reflect differences among organisms with respect to the cellular levels of NADK substrates. The high affinity of Arabidopsis NADK for CaM (S 0.5 of 2.2 nM) is consistent with reports on other plant NADKs (Harmon et al, 1984;Lee et al, 1997;Delumeau et al, 2000) and other plant CaM-binding proteins (Snedden et al, 1996;Bouche et al, 2002;Zhang et al, 2002;Chandok et al, 2003). Similarly, the S 0.5 value for Ca 21 (0.8 mM) suggests stimuli that elevate Ca 21 from resting levels in vivo may elicit a CaM-modulated NADK response.…”
Section: Discussionsupporting
confidence: 74%
“…For transcription factors of the basic-helix-loop-helix group it was reported that Ca 2ϩ /CaM binding directly inhibits their DNA binding (56). Also for the Arabidopsis transcription factors TGA3 and DL10, an interaction with CaM was shown (57,58). Therefore, one may speculate that SAURs represent an important integrative element of the cross-talk between the Ca 2ϩ /CaM messenger system and the auxin signal transduction.…”
Section: Zmsaur2 a Short-lived And Auxin-induced Nuclear Proteinmentioning
confidence: 99%
“…Glutamate is then decarboxylated to GABA by GAD. GAD has recently been identified as a Ca2+ / calmodulin-dependent enzyme (Baum et al, 1993;Snedden et al, 1996). Regulation of GAD is under developmental control (Chen et al, 1994) and has recently been proposed to play an important role in normal plant growth and development and fruit ripening (Gallego et al, 1995).…”
mentioning
confidence: 99%